2014
DOI: 10.1245/s10434-014-3805-4
|View full text |Cite
|
Sign up to set email alerts
|

A Meta-Analysis to Determine the Effect of Primary Tumor Resection for Stage IV Colorectal Cancer with Unresectable Metastases on Patient Survival

Abstract: Resection of the primary tumor may confer a survival advantage in stage IV colorectal cancer with unresectable metastases but significant selection bias exists in current studies. Randomized controlled trials are essential to validate these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
2
2

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(102 citation statements)
references
References 36 publications
7
86
2
2
Order By: Relevance
“…An intact primary site might lead to more local symptoms such as pain, further contributing to the psychological burden of the disease. Retrospective studies have suggested a possible improvement in mortality if the primary tumour is resected in the setting of advanced disease 30,31 , and prospective studies are underway to evaluate the effect of resection on overall survival, progression-free survival, and quality of life 32 . Whether performing resections in patients with advanced crc will translate into a decreased risk of suicide has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…An intact primary site might lead to more local symptoms such as pain, further contributing to the psychological burden of the disease. Retrospective studies have suggested a possible improvement in mortality if the primary tumour is resected in the setting of advanced disease 30,31 , and prospective studies are underway to evaluate the effect of resection on overall survival, progression-free survival, and quality of life 32 . Whether performing resections in patients with advanced crc will translate into a decreased risk of suicide has yet to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the proportion of patients receiving colorectal surgery is higher than had been previously reported from population-based sources. 17 There are no prospective studies to support a benefit from colectomy in patients with uncomplicated primary colorectal tumors, and the role of surgery in patients with metastatic colorectal cancer is controversial, [18][19][20] and clinical experience has shown that patients who do not receive upfront surgery infrequently require subsequent symptom-directed intervention. 21 Our study's strengths include the large, population-based cohort of patients with advanced lung and colorectal cancer, who are representative of patients diagnosed with these cancers.…”
Section: Discussionmentioning
confidence: 99%
“…When CRC is asymptomatic, the decision for surgery depends on the resectability of CRCLM. When CRCLM are non-resectable, the benefit of resection of the primary tumour without liver resection is debatable, although the results of a meta-analysis have shown a survival benefit [84]; however, data from this meta-analysis of non-randomized trials are questionable due to potential publication biases. Several RCTs have been started but most have not recruited a sufficient number of patients, and have been stopped prematurely [85].…”
Section: Surgery Of the Primary Tumourmentioning
confidence: 94%